Genetic Heterogeneity of Alicyclobacillus Strains Revealed by RFLP Analysis of vdc Region and rpoB Gene - Dekowska, Agnieszka; Sokołowska, Barbara; Niezgoda, Jolanta (BioMed research international, 2018)
PCR-RFLP targeting of the 16S rDNA and rpoB genes, as well as the vdc region, was applied to identify and differentiate between the spoilage and non-spoilage Alicyclobacillus species. Eight reference strains and 75 strains isolated from spoiled juices, juice concentrates, drinks, its intermediates, and fresh apples were subject to study. Hin6I restriction patterns of the 16S rDNA gene enabled distinguishing between all the species analyzed, while the rpoB gene and vdc gene cluster analysis also revealed that there were two major types among the A. acidoterrestris isolates, one similar to the reference strain A. acidoterrestris DSM 2498, and the other similar to the reference strain A. acidoterrestris ATCC 49025. Heterogeneity was also observed among the A. acidocaldarius isolates. RFLP analysis of the 16S rDNA and rpoB genes, as well as vdc region, can be used successfully in the identification and research of intraspecies heterogeneity of the Alicyclobacillus species.